Determination of the species and ecology of the dormouses (Myoxidae) of Artsakh and North areas of Armenia - A. M. Sargsyan (ՀՀ ԳԱԱ հրատ.)
This short communication is devoted to determination of the species and ecology of the dormouses (Myoxidae) areas of Northern Armenia and Artsakh. It was evident the presence of two species of dormouses for the mammalian fauna of Armenia: the edible dormouse (Glis glis) and the forest dormouse (Dryomys nitedula). The possibility of the third type of dormouse – garden dormouse (Eliomys quecinus) on the territory of the Republic of Armenia was discussed.Այս կարճ հաղորդագրությունը նվիրված է Հյուսիսային Հայաստանի և Արցախի քնամկների (Myoxidae) տեսակների և էկոլոգիայի որոշմանը: Հայտնի է եղել քնամկների երկու տեսակի առկայությունը Հայաստանի կաթնասունների ֆաունայում` մեծ քնամուկ (Glis glis) և անտառային քնամուկ (Dryomys nitedula): Քննարկվում է քնամկների երրորդ տիպի` այգու քնամկան (Eliomys quercinus) հնարավոր առկայությունը Հայաստանի Հանրապետության տարածքում:Это краткое сообщение посвящено определению видового состава и экологии представителей соневых (Myoxidae) Арцаха и Северных районов Армении. Было известно наличие двух видов соневых в фауне млекопитаюших Армении: сони-полчок (Glis glis) и садовой сони (Eliomys quercinus). Обсуждается наличие 3-го вида семейства соневых – садовой сони (Eliomys quecinus) н территории Републики Армения.
Keywords: Biology; Zoology; Hydrobiology